2019
DOI: 10.1111/ans.15291
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of procalcitonin for the early diagnosis of anastomotic leakage after colorectal surgery: a meta‐analysis

Abstract: Background: Anastomotic leakage (AL) is a dreaded complication following colorectal surgery. Procalcitonin is one of many biomarkers studied and research has suggested that it has improved accuracy for the diagnosis of AL compared with other inflammatory biomarkers such as C-reactive protein. This meta-analysis was conducted to evaluate the accuracy of procalcitonin in the early diagnosis of AL following colorectal surgery. Methods: MEDLINE, Embase and PubMed were searched for studies evaluating procalcitonin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…However, it remained steadily increased in G3 patients, with a markedly high mean value from POD1 to POD5. Yeung et al [ 43 ] performed the most comprehensive meta-analysis available in the literature, including nearly 7000 patients pooled from 23 studies. From POD1 to POD7, patients with CAL had a significantly higher mean CRP level compared with patients without CAL ( P < 0.001)[ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, it remained steadily increased in G3 patients, with a markedly high mean value from POD1 to POD5. Yeung et al [ 43 ] performed the most comprehensive meta-analysis available in the literature, including nearly 7000 patients pooled from 23 studies. From POD1 to POD7, patients with CAL had a significantly higher mean CRP level compared with patients without CAL ( P < 0.001)[ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yeung et al [ 43 ] performed the most comprehensive meta-analysis available in the literature, including nearly 7000 patients pooled from 23 studies. From POD1 to POD7, patients with CAL had a significantly higher mean CRP level compared with patients without CAL ( P < 0.001)[ 43 ]. In this study, CRP was the best predictor for CAL on POD4 and POD5, with a maximum AUROC of 0.81 (cut-off value of 96.8 mg/L and an NPV of 98%) on POD5.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, in a recent meta-analysis, it was concluded that PCT is a useful negative test for AL after elective colorectal surgery with negative predictive values ranging from 95% to 100% (highest AUROC was 0.88 on POD 5). But, as an isolated test, poor positive predictive values of up to 34%, limit its use in predicting AL 8 . Different from elective colorectal surgeries, in the surgical concept of gynecological malignancies (especially in advanced ovarian cancer), debulking procedures including both upper and lower abdomen and peritonectomy were needed to reach zero macroscopic residual disease to get overall survival advantage 9,10 .…”
Section: Discussionmentioning
confidence: 99%